2019
DOI: 10.1007/s11606-019-05064-w
|View full text |Cite
|
Sign up to set email alerts
|

Are We Choosing Wisely? Older Adults’ Cancer Screening Intentions and Recalled Discussions with Physicians About Stopping

Abstract: BACKGROUND: National guidelines recommend against cancer screening for older individuals with less than a 10year life expectancy, but it is unknown if this population desires ongoing screening. OBJECTIVE: To determine (1) if older individuals with < 10-year life expectancy have future intentions for cancer screening, (2) if they recall a doctor previously suggesting that screening is no longer needed, and (3) individual characteristics associated with intentions to seek screening. DESIGN: National Social life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 51 publications
1
28
0
9
Order By: Relevance
“…22 Additionally, health professionals hesitate to inform patients about confusing potential harms such as overdiagnosis 23 and the majority (around 75%) of older American adults recall no conversation with a doctor that screening for breast or prostate cancer may no longer be necessary. 19 These conversations inherently involve sensitive and uncertain topics that clinicians feel uncomfortable to raise with their older patients. 24 25 A qualitative study interviewed 40 men and women aged 65 years and older to identify their preferences for communicating about discontinuing screening.…”
Section: Introductionmentioning
confidence: 99%
“…22 Additionally, health professionals hesitate to inform patients about confusing potential harms such as overdiagnosis 23 and the majority (around 75%) of older American adults recall no conversation with a doctor that screening for breast or prostate cancer may no longer be necessary. 19 These conversations inherently involve sensitive and uncertain topics that clinicians feel uncomfortable to raise with their older patients. 24 25 A qualitative study interviewed 40 men and women aged 65 years and older to identify their preferences for communicating about discontinuing screening.…”
Section: Introductionmentioning
confidence: 99%
“…All providers in our study noted time constraints as a limiting factor to having nuanced discussions with patients regarding screening mammography. These time limitations may not only explain the lack of communication between providers and patients about screening that has been reported in prior studies ( Kotwal et al, 2019 ), but may also account for the documented variability in rates of screening mammography utilization ( Martires et al, 2014 , Linder et al, 2014 ). Decision fatigue is a term that describes the phenomenon in which providers are more willing to order healthcare services of questionable utility later in the day when appointment time is limited.…”
Section: Discussionmentioning
confidence: 97%
“…Second, study findings reflect self-reported data from participants and may not accurately reflect their clinical practice, as prior work has demonstrated that PCP verbalized endorsement of shared decision-making does not always correspond to actual clinical practice. 47 Importantly, selection bias and/or response bias may have contributed to our finding that all interviewed providers frequently engaged in shared decision-making with their patients regarding screening mammography, as prior literature has demonstrated few patients recall engaging in such discussions with their PCP ( Kotwal et al, 2019 ). Finally, the majority of our participants were medical doctors and thus our data may not reflect the views of advanced practice providers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may help ameliorate a key challenge to changing screening behavior: patients tend to overestimate the benefits and underestimate the potential harms of screening. 25 Mutual understanding of the purpose of screening at the time screening is first recommended, reiterated over time, will help facilitate meaningful end-of-screening discussions by reinforcing realistic risk/benefit expectations. Clinicians will also benefit from clinical practice guidelines with a framework for approaching screening decisions with patients, such as the Individualized Decisions for Screening framework proposed by Breslau et al 23 End-of-screening discussions can be time-consuming; including end-of-screening discussions in quality metrics will help ensure that health systems adjust scheduling expectations and compensation schemes to accommodate this.…”
Section: Discussionmentioning
confidence: 99%